Role of the amazon outflow on the barotropic tide on the amazonian shelf. (1st April 2022) - Durand, Fabien; Testut, Laurent; Jouanno, Julien; Fassoni-Andrade, Alice César
Abstract: The Amazon yields the largest freshwater discharge to the world ocean, outflowing on a shallow, macro-tidal shelf. Its plume dynamics is complex and the impact of the discharge on the tidal properties on the adjoining shelf remains poorly understood. Through a series of numerical modelling experiment, we investigate the interaction between the Amazon discharge and the tide over the Amazonian shelf. We find that the runoff is responsible for a rise of the M2 tidal amplitude of ten cm in the embayment between Cabo Norte and Cabo Cassipore. The runoff also induces a rise of the mean sea level there, of 10 cm as well. Such a one-to-one sensitivity of the tidal amplitude and of the mean sea level over this region is quite unique among the world coastline. The modulation of the bottom friction by the thickness of the water column as well as by the vertical density stratification in the Amazon plume appears to be the main forcing factor of this response. Our numerical sensitivity experiments suggest that the seasonal variability of the Amazon discharge has little impact on the temporal variability of the tidal characteristics over the Amazonian shelf. Highlights: A numerical study of the impact of the Amazon discharge on the magnitude of the tide at its mouth. The discharge induces a rise of tidal amplitude of 10 cm at the coast. This rise is associated to a rise of mean sea level also of ten centimeters 10 cm. This tidal amplification is partly attributable to the rise of mean sea level. It is also partly attributable to the vertical density stratification of the Amazon plume.